Mandibular Reconstruction Using a Customized Three-Dimensional Titanium Implant Applied on the Lingual Surface of the Mandible. Issue 2 (March 2018) - Jo, You-Young; Kim, Seong-Gon; Kim, Min-Keun; Shin, Sung-Ho; Ahn, Janghoon; Seok, Hyun
Abstract : Abstract: A patient had a right mandibular defect due to resection of an ameloblastoma. Previously, the defect had been reconstructed by an iliac bone graft, and subsequently, a titanium mesh with xenograft was used. However, it was not successfully reconstructed. For the recovery of mandible continuity and rehabilitation of jaw movement, we manufactured a customized 3-dimensional titanium implant by computer-aided design and manufacturing and electron beam melting technology. This implant was designed to have a porous body structure and lingual plate. The customized implant was accurately inserted in the bony defect. As a result, the patient showed a normal range of mouth opening and jaw movement. New bone migration was observed in the porous structure of the implant. Although there was a slight plate exposure and lack of alveolar bone formation, the customized 3D titanium implant successfully reconstructed the mandibular discontinuous defect and recovered jaw movement. Abstract : Supplemental Digital Content is available in the text